Spirituality and practice of the euphemism in the workplace: perceptions of a nursing team - Edilaine Maran; Laura Misue Matsuda; Dandara Novakowski Spigolon; Elen Ferraz Teston; Edna dos Santos Almeida; Patrícia Amara da Silva; Sonia Silva Marcon
ABSTRACT Objectives: to understand the spirituality and the practice of euphemism experienced by nursing professionals in the hospital scenario. Methods: a descriptive, exploratory research with a qualitative approach, carried out with 18 nursing professionals from a hospital in southern Brazil. Data collection took place from September to October 2018, through recorded audio interviews. The reports were submitted to thematic content analysis and the discussion was based on the theory of transpersonal care. Results: four categories emerged from the speeches: Motivational reflection of spirituality in the work environment; Adherence to the practice of euphemism by nursing professionals; Satisfaction and frustration in the practice of euphemism by nursing professionals and; Spirituality as an increase in human faith. Final Considerations: professionals understand spirituality and the practice of euphemism as a tool that helps in motivating the team to face difficulties at work and increase the faith of hospitalized patients.